STRATEGI PEMBELAJARAN SENAM IRAMA ANAK USIA 5-6 TAHUN DI TK RAUDHATUL MUHTADIN - Ghita Sri Cahyati; Aunurrahman Aunurrahman; Dian Miranda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to find out how rhythmic gymnastic learning strategies in developing childern’s muscle strength, childern’s flexibility, childern’s agility and childern’s balance. In the gross motor skills of childern learning to move the whole body, then the method used is a method of activities that can spur all the rought activities that need to be developed by childern such as childern can learn gymnastic movements,catching the ball, kicking, jumping and so forth. Gymnastics is a child’s gross motor development activities that can be learned in early childhood. Rhythmic gymnastics applied by the teacher is very helpful in the process of grow motor development of childern, especially children aged 5-6 years, childern are able to follow coordinated exercise movements such as stretching hands, walking in place, small jumps, swinging hands to the right and left, following the appropriate gymnastic movements the rhythm of the song is not late nor the speed according to the teacher’s guide. The gross motor development reffered to in this study is the gross motor development of childern aged 5-6 years that will be developed namely developing the strength of childern with small jumping movements, developing the flexibility of childern by swinging their arms, developing the flexibility of childern ith small jogging movement in place, develops a child’s balance by standing on one leg.       Keywords : Rhytmic Gymnastic, Gross Motor Skills, Childern Ages 5-6 Years